2010
DOI: 10.2110/jsr.2010.066
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Geology and Human Origins: A Fresh Look at Olduvai Gorge, Tanzania

Abstract: Recent field work at Olduvai Gorge (Tanzania) using sedimentary geology, in particular high-resolution paleoenvironmental reconstruction and isotope geochemistry, has revealed that freshwater was in proximity to a number of the rich fossil sites in Beds I and II (, 2.0-1.0 Ma). This paper presents the first geological evidence for springs associated with archaeological sites in this semiarid rift basin. The springs appear to be limited to a small area within the basin and were likely connected to faults that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…For Lower Paleolithic sites, in particular, it is commonly ambiguous as to whether the sites represent environments favored by early humans or represent environments with favorable preservation potential (Hijma et al, 2012). Most Paleolithic open-air sites are associated with either fluvial or lacustrine environments (Ashton et al, 2006;Bridgland et al, 2006;Preece et al, 2006;Ashley et al, 2010). Ashton et al (2006) suggested that early humans favored fluvial environments due to a greater variety of resources (plants, animals, lithic raw material) compared to lacustrine settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Lower Paleolithic sites, in particular, it is commonly ambiguous as to whether the sites represent environments favored by early humans or represent environments with favorable preservation potential (Hijma et al, 2012). Most Paleolithic open-air sites are associated with either fluvial or lacustrine environments (Ashton et al, 2006;Bridgland et al, 2006;Preece et al, 2006;Ashley et al, 2010). Ashton et al (2006) suggested that early humans favored fluvial environments due to a greater variety of resources (plants, animals, lithic raw material) compared to lacustrine settings.…”
Section: Discussionmentioning
confidence: 99%
“…During the rather dry and cold early and late phases of the Holsteinian stage in particular, the wetland of the delta plains probably represented a flourishing ecosystem within a rather dry and hostile environment (cf. Oviatt et al, 2003;Preece et al, 2006;Yansa, 2007;Ashley et al, 2008Ashley et al, , 2010. Even the shores of proglacial lakes have been recognized as inhabitable sites for early hunter-gatherers (Overstreet and Kolb, 2003;Hill, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In an otherwise inhospitable landscape these local freshwater pools may have provided important freshwater resources for hominins. Ashley et al (2009Ashley et al ( , 2010 found freshwater carbonates associated with several fossil-and artifactrich sites in Olduvai Beds I and II and speculate that groundwater-fed springs and wetlands (Deocampo et al, 2002) have been sourced via faults that transect the basin. This might suggest that the northeast-southwest trending faults were hydraulically active during Upper Bed I/lowermost Bed II, fitting with the regional east-west extensional tectonic regime during the Pleistocene.…”
Section: Discussionmentioning
confidence: 99%
“…The microfaunal analysis of Level 20 at FLK NW, situated between FLK and FLK NN, as described in Arcos-Fernández et al's paper, shows that trees were a conspicuous feature of the landscape. This is further supported by the analysis of paleobotanical remains at the top of the sequence (FLK N level1-2), where the paper by Ashley et al on the reconstruction of the paleolandscape during FLK N times shows the presence of a wetland created by the same spring system as at FLK Zinj (see also Ashley et al, 2010). The paper by Barboni et al provides a detailed description of over 140 different species of plants, among which trees are predominant, around FLK N. This indicates that although open landscape could potentially have been predominant along the gorge, especially south of the gorge junction (Bamford et al, 2008), the area surrounding FLK N was heavily wooded and perhaps even forested.…”
Section: Introduction To the Special Issue On Olduvai Gorgementioning
confidence: 70%